Emerging Threat of Oxyrachis tarandus Fabricus Infestation on Banyan Trees (Ficus benghalensis Linnaeus) - Gouda, M. N. Rudra; Pavan, J. S.; Raiza Nazrin, M. R.; Sharath, R. (International Journal of Economic Plants, 2024)
A comprehensive survey was conducted during March 2022– October 2023 in various forest areas including Pusa Hill Forest, Alipur City Forest, and Jahanpanah City Forest, New Delhi, India to study Oxyrachis tarandus, cow horn bug or treehopper on Ficus benghalensis. This study utilized both morphological and molecular techniques for accurate species identification, revealing a significant association between O. tarandus and F. benghalensis. Morphological identification relied on established criteria, which included measurements of adult insects and the observation of distinctive features such as wings and horns. On the other hand, molecular identification involved DNA extraction from collected specimens, followed by PCR amplification targeting a fragment of the MT-COI gene. This approach facilitated precise species identification and allowed for the construction of a phenogram to analyze genetic relationships within the studied population. Phenogram construction and analysis were conducted to further validate species identification and explore genetic relationships. The treehopper’s feeding behaviour, oviposition habits, and ecological interactions were thoroughly documented, highlighting its potential impact on the banyan tree’s health and ecosystem dynamics. This information underscored the necessity for ongoing monitoring and development of effective pest management strategies to conserve India’s national tree and forest biodiversity. The study revealed the critical need for ongoing research and conservation efforts to address pest-induced threats to iconic tree species like F. benghalensis, thereby ensuring the long-term health and resilience of forest ecosystems.